ANALISIS KESULITAN SISWA DALAM MELUKIS LINGKARAN DALAM DAN LINGKARAN LUAR SEGITIGA PADA MATERI GARIS SINGGUNG LINGKARAN KELAS VIII MTs ASSHOLACH - Uswatun Hasanah (Universitas Nahdlatul Ulama Pasuruan, 2023)
Uswah, Hasanah. 2023 Analysis of Students' Difficulties in Painting Inner Circles and Outer Circles of Triangles on Material Tangents to Circles Class VIII MTs Assholach. Mathematics Education Study Program, Faculty of Education, Pasuruan Nahdlatul Ulama Institute of Technology and Science. Keywords: Painting Difficulty, Inner Circle of Triangles, Outer Circles of Triangles. Geometry is a branch of mathematics that is taught at all levels of education in Indonesia, starting from elementary school to university. Geometry is a branch of mathematics that is difficult to learn, one of the basic geometry skills that students must master is drawing skills or painting pictures. Among them are painting the inner circle and the outer circle of the triangle. This research is a type of descriptive qualitative research that aims to describe students' difficulties in painting the inner circle and outer circle of triangles on material tangent to the circle of MTs students. The subjects in this study were students of class VIII MTs Assholach consisting of 3 students. The criteria for selecting subjects were subjects who had studied the material tangent to a circle. The selection of the subject was based on several considerations, namely: (1) students who have high, medium and low ability levels based on ability tests, and (2) communicative students based on recommendations from teachers at the research site and are willing to work together to help achieve research goals. The instruments in this study were the researchers themselves and the test sheets as the main instruments guided by interview guidelines and tape recorders. Data collection was carried out by conducting written tests and interviews. Data analysis used source triangulation, the inner circle and outer circle painting tests were carried out with different subjects at the same time. The conclusions in this study were 1) difficulty painting using compasses, 2) difficulty drawing bisectors, 3) difficulty drawing axis lines, 4) difficulty determining the radii and intersection points of the inner circle and outer circle of triangles, 5) do not know the concept of painting the inner and outer circles of a triangle, and 6) difficulty distinguishing between the inner and outer circles of a triangle.